Fu-zi decoction attenuate rheumatoid arthritis in vivo and in vitro by modulating RANK/RANKL signaling pathway - Pan, Zhenzhen; Li, Fangchan; Xu, Yujie; Ye, Huimin; Liu, Jiahui; Wang, Zhenhua; Deng, Changsheng; Song, Jianping; Mei, Manxue; Li, Changqing (Frontiers in Pharmacology, 2024)
Background: Fu-zi decoction (FZD) has a long history of application for treating Rheumatoid arthritis (RA) as a classic formulation. However, its underlying mechanisms have not been fully elucidated. This study aimed to decipher the potential mechanism of FZD in treating RA, with a specific focus on receptor activator of nuclear factor κB/receptor activator of nuclear factor κB ligand (RANK/RANKL) signaling pathway.The impact of FZD on RA was investigated in collagen-induced arthritis rats (CIA), and the underlying mechanism was investigated in an osteoclast differentiation cell model. In vivo, the antiarthritic effect of FZD at various doses (2.3, 4.6, 9.2 g/kg/day) was evaluated by arthritis index score, paw volume, toe thickness and histopathological examination of inflamed joints. Additionally, the ankle joint tissues were determined with micro-CT and safranin O fast green staining to evaluate synovial hyperplasia and articular cartilage damage. In vitro, osteoclast differentiation and maturation were evaluated by TRAP staining in RANKL-induced bone marrow mononuclear cells. The levels of pro-and anti-inflammatory cytokines as well as RANKL and OPG were evaluated by ELISA kits. In addition, Western blotting was used to investigate the effect of FZD on RANK/RANKL pathway activation both in vivo and in vitro.Results: FZD significantly diminished the arthritis index score, paw volume, toe thickness and weigh loss in CIA rats, alleviated the pathological joint alterations. Consistent with in vivo results, FZD markedly inhibited RANKL-induced osteoclast differentiation by decreasing osteoclast numbers in a dose-dependent manner. Moreover, FZD decreased the levels of pro-inflammatory cytokines IL-6, IL-1β and TNF-α, while increasing anti-inflammatory cytokine IL-10 level both in serum and culture supernatants. Treatment with FZD significantly reduced serum RANKL levels, increased OPG levels, and decreased the RANKL/OPG ratio. In both in vivo and in vitro settings, FZD downregulated the protein expressions of RANK, RANKL, and c-Fos, while elevating OPG levels, further decreasing the RANKL/OPG ratio.In conclusion, FZD exerts a therapeutic effect in CIA rats by inhibiting RANK/RANKL-mediated osteoclast differentiation, which suggested that FZD is a promising treatment for RA.